ANALISIS IMPLEMENTASI KEBIJAKAN DINAS SOSIAL DAN PEMAKAMAN KOTA PEKANBARU TENTANG ANAK JALANAN - Try Wiganda Irfan Wiganda Irfan; Sri Erlinda Sri Erlinda; Zahirman Zahirman ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Absract : This research is motivated because of the growing number of street children in the city of Pekanbaru from year to year were forced to take to the streets for food just to survive. In accordance with the policy of the Department of Social and Funeral Pekanbaru against street children is a coaching program. Formulation of the problem in this research is how the implementation of policies and the Social Service Pekanbaru City Cemetery on Street Children. This study aims to determine the policy implementation of Social Service and Burial Pekanbaru on Street Children. As for the population in this study is the Employees Social Service and Funeral Pekanbaru and street children Pekanbaru totaling 560 people, while the sample in this study is the Head of Service and Social Empowerment as many as 1 person, Head of Section for Child Welfare Family and the elderly as much as one person, the coach street children as much as one person, and street children as many as 53 people. A sampling technique that uses a technique purposive sampling area. The technique of collecting data were collected through observation, interviews, questionnaires, literature, and documentation. The results showed that the Social Service Policy Implementation Analysis and Funeral Pekanbaru About Street Children answer